Thermal responses of face-masked pedestrians during summer: An outdoor investigation under tree-shaded areas. (1st April 2023) - Zhang, Yuchun; He, Huiyu; Dai, Kunquan; Lin, Zhang; Fang, Zhaosong; Zheng, Zhimin
Abstract: During the SARS-CoV-2 (COVID-19) pandemic, most citizens were cooperative towards the face-masking policy; however, undeniably, face masking has increased complaints of thermal discomfort to varying degrees and resulted in potential health hazards during summer. Thus, a thermal comfort survey was conducted under tree-shaded areas generally preferred by pedestrians to explore the thermal response of face-masked pedestrians. Thirty-two subjects, with and without masks, participated in walking experiments, and their thermal parameters and physiological indicators were recorded; moreover, the subjects were asked to fill in subjective questionnaires. The results showed that although tree shades significantly reduced the average radiant temperature, dampness in the mask may cause some discomfort symptoms, among which intense sweating (54.55%) and tachycardia (42.18%) accounted for the largest proportion. Based on thermal indices, it could be concluded that face-masking does not significantly affect the thermal comfort of subjects walking in shaded areas. Notably, a 30-min walk in tree-shaded areas with face masking does not adversely affect human health or quality of life. Thus, the present assessment of the thermal safety of humans in shaded environments provides reference data for determining thermal comfort levels during outdoor walking with face masking. Highlights: The subjects wear face masks to simulate to explore the thermal response of face-masked pedestrians. The differences of thermal sensation between wear masks and without masks while walking are determined. The human body, while walking, was less sensitive to wetness than hotness. Tsk could predict the thermal sensation of the human body while walking.